Improving attentional processes in sport: classifications of exercises and principles of development of attentional skills - Schefke, T.; Gronek, P. (Studies in Physical Culture and Tourism, 2011)
In our search for hints and ideas on improving attentional processes in sport, we analyzed in previous articles the concept of attention and differentiated between various types of attention and attentional skills. We also tried to identify sport specific issues of attention, using a comparative case study of tennis. In this paper we want to suggest another possible attitude, i.e. studying various exercises and ideas used to or recommended to improve attention in sports. This approach, which appraises the art of attention improvement, combined with the theoretical analysis conducted in previous articles, has enabled us to develop several classifications of attentional exercises, identify environmental factors stimulating and challenging attention and finally define principles of development of attentional skills.